Factor structure of DSM-5 PTSD symptoms in trauma-exposed adolescents: Examining stability across time. (December 2017) - Wang, Li; Cao, Xing; Cao, Chengqi; Fang, Ruojiao; Yang, Haibo; Elhai, Jon D.
Highlights: A 7-factor hybrid model fit significantly better than other alternative DSM-5 PTSD models at Wave 1. A 7-factor hybrid model fit significantly better than other alternative DSM-5 PTSD models at Wave 2. The 7-factor hybrid model demonstrated the longitudinal invariance across time. Abstract: This study investigated the latent structure of DSM-5 PTSD symptoms using two-wave longitudinal data collected from a sample of adolescents exposed to an explosion accident. Two waves of surveys were conducted approximately 3 and 8 months after the accident, respectively. A total of 836 students completed the baseline survey, and 762 students completed the follow-up survey. The results of confirmatory factor analyses(CFA) indicated that a seven-factor hybrid model composed of intrusion, avoidance, negative affect, anhedonia, externalizing behaviors, anxious arousal and dysphoric arousal factors yielded significantly better data fit at both waves than the other models including the DSM-5 four-factor model, the six-factor anhedonia and externalizing behaviors models. Furthermore, the results of CFA invariance tests supported the longitudinal invariance of the model. Implications and limitations in terms of these results are discussed.